Large-Scale Assessment of Soil Physical Quality of Rural Settlements in the Southeast of Goiás, Brazil - Anderson Rodrigo Da Silva; Wênio Vieira; Ítalo Rômulo Mendes de Souza (Applied and Environmental Soil Science)
Land use and soil physical quality are related. In this work, the S index was used to evaluate the physical quality of the soils of three rural settlement units located in the Brazilian Cerrado, with areas ranging from 700 to more than 4000 hectares, based on a novel method. To map the S index, a set of pedotransfer functions for water retention curves was adapted according to a broad range of clay content for Cambisols, in three depth layers. Some rural units presented associations with classes of land use. In general, deeper layers presented higher values of S. In areas with less than 370 g/kg of clay, land uses that provide low soil cover should be avoided to prevent physical degradation.